2012
DOI: 10.1111/j.1365-2133.2012.11000.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-4 genetic variants correlate with its transcript and protein levels in patients with vitiligo

Abstract: Our results suggest that these polymorphisms of the IL4 gene may be genetic risk factors for susceptibility towards vitiligo and the upregulation of the IL4 transcript, protein and IgE levels in individuals with susceptible haplotypes reveal the crucial role of IL-4 in the pathogenesis of vitiligo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(38 citation statements)
references
References 38 publications
2
33
1
Order By: Relevance
“…Recently, we have shown positive association of HLA-A*33:01, HLA-B*44:03, and HLA-DRB1*07:01 with vitiligo patients from North India and Gujarat suggesting an autoimmune link of vitiligo in these cohorts [22]. The genotype-phenotype correlation of CTLA -4 and IL -4 gene polymorphisms also supported the autoimmune pathogenesis of vitiligo in Gujarat population [23],[24], whereas our earlier studies on MBL -2, ACE, PTPN 22 polymorphisms did not show significant association [25][27].…”
Section: Discussionmentioning
confidence: 52%
“…Recently, we have shown positive association of HLA-A*33:01, HLA-B*44:03, and HLA-DRB1*07:01 with vitiligo patients from North India and Gujarat suggesting an autoimmune link of vitiligo in these cohorts [22]. The genotype-phenotype correlation of CTLA -4 and IL -4 gene polymorphisms also supported the autoimmune pathogenesis of vitiligo in Gujarat population [23],[24], whereas our earlier studies on MBL -2, ACE, PTPN 22 polymorphisms did not show significant association [25][27].…”
Section: Discussionmentioning
confidence: 52%
“…We have also shown that the three most significant class II region SNPs: rs3096691 (just upstream of NOTCH4), rs3129859 (just upstream of HLA-DRA), and rs482044 (between HLA-DRB1 and HLA-DQA1) are associated with generalized vitiligo in Indian population [29]. The genotype-phenotype correlation of CTLA4, IL4 and TNFA gene polymorphisms also supported the autoimmune pathogenesis of vitiligo in Gujarat population whereas our earlier studies on CAT, GPX, MBL2, ACE, and PTPN22 polymorphisms did not show significant association [30][31][32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 66%
“…Hernanz et al [68] reported that NPY enhanced the production of IL6 and TNFα in peripheral blood cells. In addition, our previous studies have shown high levels of serum IL4 and TNFα as well as increased mRNA levels in patients with vitiligo compared to controls [62], [63] suggesting that NPY might be involved in the cell-mediated as well as humoral immune mechanisms and plays a crucial role in melanocyte destruction. However, the exact role of NPY in vitiligo pathogenesis is yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%